Ybytyramoan, a new genus of fireflies (Coleoptera: Lampyridae, Lampyrinae, Photinini) endemic to the Brazilian Atlantic Rainforest, with description of three new species - Da Silveira, Luiz Felipe Lima; Mermudes, José Ricardo M. (Zootaxa, 2014)
Here we describe a new Photinina genus with three species endemic to Serra dos Órgãos Mountains in Brazil. Ybytyramoan gen. nov. occurs in high altitudes, from 980m up to 2000m, and has the following unique set of characters: head abruptly depressed at vertex; lanterns not fully developed, somewhat rounded or anteriorly rounded, straight posteriad, with posterolateral rounded projections (billycock-shaped), at the middle of the abdominal sterna VI and VII; abdominal sternum VIII not covered by VII; phallus and parameres apically teethed. We provide illustrations and a key to the three species in this genus: Ybytyramoan praeclarum sp. nov. (type-species), Y. diasi sp. nov., Y. monteirorum sp. nov.